Удосконалення правового регулювання провадження в справах про порушення митних правил. - Нижникова, В.В.; Нижникова, В.В.; Nizhnikova, V. (My University, 2012)
Certain problems of procedural legal settlement on cases of customs regulation violation are considered in the article. It is concluded that most of the problem questions arising in the process of customs bodies activities connected with bringing to administrative responsibility for customs regulation violation is caused by a great number of gaps and contradictions in normative regulation of corresponding delinquent relations. In this connection a number of propositions concerning the introducing of changes and additions of certain articles to section 19 of Customs Code of Ukraine that set rules of procedure on cases of customs regulation violation is formulated.
Нижникова В.В. Удосконалення правового регулювання провадження в справах про порушення митних правил. / В.В.Нижникова //Актуальні проблеми політики : зб. наук. пр. / гол. ред. С. В. Ківалов ; відп. за вип. Л. І. Кормич. – Одеса : Національний університет "Одеська юридична академія" : Південноукраїнський центр гендерних проблем, 2012. – Вип. 44. – C. 366 - 375.
Keywords: Порушення митних правил; Провадження в справах про порушення митних правил; Внесення змін та доповнення конкретних статей ХIХ розділу Митного кодексу України; Удосконалення правового порушення митних правил; Усовершенствование правового нарушения таможенных правил; Внесение изменений и дополнений конкретных статей XIX раздела Таможенного кодекса Украины; Производство по делам о нарушении таможенных правил; Нарушение таможенных правил; Violation of customs regulations; Proceedings on violation of customs regulations; Changes and additions to the specific section of Article XIX of the Customs Code of Ukraine; Improvement of the legal violation of customs regulations